nvestigating grade 10 English language teachers’ experiences of implementing inclusive education in three schools in Johannesburg under Covid-19 pandemic conditions - Adewunmi, Maryam Chinasa (My University, 2022)
The Covid-19 pandemic began in late 2019 in the Chinese city of Wuhan and spread to South Africa in 2020. The pandemic resulted in the government limiting the size of public gatherings, closing borders, imposing travel restrictions, as well as school closures. The consequent lockdown resulted in an educational shift away from the traditional teaching process and toward remote teaching. Since then, the educational sector has faced enormous challenges in the context of the Covid-19 pandemic in implementing inclusive education. This study looks at six (6) Grade 10 English language teachers' experiences implementing inclusive education in three schools under the covid-19 pandemic. This study used the emancipation/transformation and critical approaches of the social model paradigm of inclusive education to understand the implementation of inclusive education in schools from quintiles one, three and five under pandemic conditions. The study followed the qualitative approach to research. Two teachers in each of the three schools were interviewed telephonically, and the data was analysed thematically. All teachers indicated that, they were not able to implement inclusive education because of the challenges they experienced under Covid-19 pandemic conditions. The findings also indicated that they seemed to incline more toward a special education approach, although ideologically, they all seemed to accept the inclusive educationof the social model approach.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education in Inclusive Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022